Potential of Beetroot and Blackcurrant Compounds to Improve Metabolic Syndrome Risk Factors - Haswell C; Ali A; Page R; Hurst R; Rutherfurd-Markwick K (MDPI (Basel, Switzerland))
Metabolic syndrome (MetS) is a group of metabolic abnormalities, which together lead to increased risk of coronary heart disease (CHD) and type 2 diabetes mellitus (T2DM), as well as reduced quality of life. Dietary nitrate, betalains and anthocyanins may improve risk factors for MetS and reduce the risk of development of CHD and T2DM. Beetroot is a rich source of dietary nitrate, and anthocyanins are present in high concentrations in blackcurrants. This narrative review considers the efficacy of beetroot and blackcurrant compounds as potential agents to improve MetS risk factors, which could lead to decreased risk of CHD and T2DM. Further research is needed to establish the mechanisms through which these outcomes may occur, and chronic supplementation studies in humans may corroborate promising findings from animal models and acute human trials.
© 2021 by the authors
Keywords: anthocyanins; dietary nitrate; betalains; hyperglycemia; hypertension; dyslipidemia; diabetes; glucose control; 0301 Analytical Chemistry; 0601 Biochemistry and Cell Biology; 1103 Clinical Sciences